Iterative Reconfigurable Tree Search Detection of MIMO Systems. (12th September 2006) - Zheng Zheng, Wu Wu; Song Song, Wentao Wentao; Luo Luo, Hanwen Hanwen; Liu Liu, Xingzhao Xingzhao
Abstract : This paper is concerned with reduced-complexity detection, referred to as iterative reconfigurable tree search (IRTS) detection, with application in iterative receivers for multiple-input multiple-output (MIMO) systems. Instead of the optimum maximum a posteriori probability detector, which performs brute force search over all possible transmitted symbol vectors, the new scheme evaluates only the symbol vectors that contribute significantly to the soft output of the detector. The IRTS algorithm is facilitated by carrying out the search on a reconfigurable tree, constructed by computing the reliabilities of symbols based on minimum mean-square error (MMSE) criterion and reordering the symbols according to their reliabilities. Results from computer simulations are presented, which proves the good performance of IRTS algorithm over a quasistatic Rayleigh channel even for relatively small list sizes.